Le culte d’Ifá ou les recompositions du champ religieux afro-latino-américain - Stefania Capone (Caravelle)
This article discusses the corrections that should be taken into consideration about the Afro-Latin-Americain religious field from the exemplary case of the introduction of Cuban’s traditional Ifa’s cult into Brazilian candomblé. The ritual negotiation generated in Brazil by the meeting of different regional modes – Nigerian, Cuban and Brazilian – of Orishas’ cult, highlights the challenges of a religious transnationalisation which deeply modifies the balance, often fragile, among the characteristics of Afro-American cultures.